Dexamethasone versus placebo for prevention of nausea, vomiting and pain after open total abdominal hysterectomy. (19th May 2022) - Kashanian, Maryam; Javanmanesh, Forough; Rokhtabnak, Faranak; AmirZargar, Shahla; Sheikhansari, Narges; Abdollahi, Hoda
Abstract: Post-operative nausea and vomiting (PONV) is a disturbing issue. Dexamethasone has been suggested for the prevention of PONV. The aim of the present study was to evaluate the efficacy of dexamethasone as an anti-emetic and analgesic following total abdominal hysterectomy. The study was performed as a double blind, placebo-controlled randomised clinical trial on 102 women undergoing an open total abdominal hysterectomy. The intervention group received 8 mg dexamethasone 1 h before surgery, and the control group received a placebo. The total number of emesis episodes during the 24 h after surgery did not show significant difference between the two groups, however, the number of emesis episodes in hours 2 and 4 after the surgery were less in the intervention group, but not in hours 0, 6, 12 and 24. The nausea severity in hours 0, 2, 4, 6 and 12 after the surgery, was less in the intervention group. The severity of pain was not different between the two groups. IMPACT STATEMENT: What is already known on this subject? Post-operative nausea and vomiting (PONV) is an important and disturbing issue. It is one of the most common problems following gynaecological surgeries including open total abdominal hysterectomy (TAH). Dexamethasone has been suggested as a prophylaxis for the prevention of PONV. What do the results of this study add? Dexamethasone 8 mg is effective for the prevention of late onset PONV (after 2 h of surgery) in the cases of open total abdominal hysterectomy. However, it has no effect on PONV immediately following surgery (hour 0) and pain. What are the implications of these findings for clinical practice and/or further research? Dexamethasone can be considered as an effective prophylaxis for PONV for the first 24 h after an open total abdominal hysterectomy, but it has limited effects on the management of early onset of PONV; between 0 and 2 h after surgery. Since the highest rates of emesis episodes and nausea severity are at this time, it is suggested to combine another rapid onset medication with dexamethasone. Also, dexamethasone, 8 mg, cannot be considered for pain relief after an open total abdominal hysterectomy. Higher amounts of dexamethasone should be evaluated for this purpose, in order to find appropriate dosages.